Impact of homoarginine on myocardial function and remodeling in a rat model of chronic renal failure - Koch, Vitali; Weber, Christophe; Riffel, Johannes; Buchner, Kristina; Buß, Sebastian Johannes; Hein, Selina; Mereles, Derliz; Hagenmüller, Marco; Erbel, Christian; März, Winfried; Booz, Christian; Albrecht, Moritz Hans Ernst; et al. (Journal of cardiovascular pharmacology and therapeutics, 2022)
Purpose:Low plasma concentrations of the amino acid homoarginine (HA) have been shown to correlate with adverse cardiovascular outcome, particularly in patients with chronic kidney disease. The present study sought to investigate the effect of HA treatment on cardiac remodeling in rats undergoing artificially induced renal insufficiency by 5/6 nephrectomy (5/6 Nx).Methods:A total of 33 male Wistar rats were randomly divided into sham and 5/6 Nx groups, receiving either placebo treatment or 400 mg·kg?1·day?1 HA over a 4-week period.Results:5/6 Nx per se resulted in adverse myocardial remodeling with aggravated cardiac function and associated cardiac overload as the most obvious alteration (?23% ejection fraction, P < 0.0001), as well as increased myocardial fibrosis (+80%, P = 0.0005) compared to placebo treated sham animals. HA treatment of 5/6 Nx rats has led to an improvement of ejection fraction (+24%, P = 0.0003) and fractional shortening (+21%, P = 0.0126), as well as a decrease of collagen deposition (?32%, P = 0.0041), left ventricular weight (?14%, P = 0.0468), and myocyte cross-sectional area (?12%, P < 0.0001). These changes were accompanied by a downregulation of atrial natriuretic factor (?65% P < 0.0001) and collagen type V alpha 1 chain (?44%, P = 0.0006). Sham animals revealed no significant changes in cardiac function, myocardial fibrosis, or any of the aforementioned molecular changes after drug treatment.Conclusion:Dietary HA supplementation appears to have the potential of preventing cardiac remodeling and improving heart function in the setting of chronic kidney disease. Our findings shed new light on HA as a possible new therapeutic agent for patients at high cardiovascular risk.
Gesehen am 07.10.2022